Psycho-socio-cultural determinants for the implementation of telemedicine projects in Senegal - Schryvers, Ellen; Verbeke, Frank (Journal of Health Informatics in Africa, 2024)
Background and objective: A teleconsultation solution for gyneco-obstetrics and neonatology in the Sokone region (Senegal) is proposed for implementation in the very near future. The intention is to use smart glasses to bring clinical expertise into the health center and health posts, with the goal of improving the quality and accessibility of health care and streamlining numerous referrals. But this has psychological implications for both the patient and the health care provider. Field experience, confirmed by the literature, tells us that the successful implementation of such telemedicine solutions depends in part on their proper integration into the socio-cultural environment of the country or region. A field mission was conducted to understand this local context and to document the main socio-cultural risk factors as well as the elements that promote the adoption and use of telemedicine applications in the region. Methods: Qualitative data collection was conducted through 4 focus groups and 2 in-depth interviews. To develop the interview guide, we drew on previous studies on the implementation and use of telemedicine applications. The following themes were addressed: (1) main benefits, (2) expected barriers, (3) who makes the decision to use, (4) costs of triangular consultation, (5) accountability for medical decisions, and (6) other potential applications of smart glasses. Results: The importance of on-site care, the quality of patient management, and the importance of smart glasses in emergencies are considered the main benefits for the region. The expected barriers can be broken down into 8 dimensions: financial, infrastructural, organizational, technological, cultural, individual, regulatory, and healthcare-related. The shared responsibility of the on-site provider and the remote physician for medical decisions made in a triangular consultation, as well as the financial allocation so that physicians are properly compensated for their services, are important issues that must have a legal basis. Finally, the participants see other opportunities in the use of the glasses, such as a tool for remote training and supervision. Conclusion: We can conclude that there is a great deal of enthusiasm, both among caregivers and patients, for the implementation of these smart glasses. It is expected that they will provide many benefits to the region in terms of quality of health care. But the focus groups also provided important information about the local context. In addition, the organization of the focus groups created a dynamic among the participants. Future users will feel involved and heard. We are aware that testing these results using a qualitative method would add value. There would be more support for the results and even more people would feel involved in the implementation process.